Pengaruh Self Esteem dan Rasa Syukur Terhadap Optimisme Studi di MA Hidayatullah: Self Esteem, Rasa Syukur, Optimisme - Fitriyani, Nur; Lilik Sriyanti (Counseling As Syamil Jurnal Ilmiah Bimbingan Konseling Islam, 2025)
Abstract: The purpose of this study was to determine; (1) the effect of self-esteem on optimism, (2) the effect of gratitude on students' optimism, (3) the effect of self-esteem and gratitude on optimism. This study used a quantitative correlational method. Data were collected through a psychological scale of self-esteem totaling 19 items, a psychological scale of gratitude totaling 29 items, and a psychological scale of optimism totaling 35 items that had been tested for expert judgment, tested for validity and reliability so that they were suitable for use. The number of samples taken was 76 which were selected using simple random sampling from a total population of 318 MA Hidayatullah students. Data analysis used multiple linear regression to determine the effect of self-esteem and gratitude on students' optimism. This study found that self-esteem had an effect on optimism with a coefficient value of 0.280 and a sig value of 0.046 <0.05. Then gratitude had a significant effect on optimism with a coefficient value of 0.757 and a sig value of 0.000 <0.05. Self-esteem and gratitude have a positive and significant influence on students' optimism by 53.7%, with self-esteem contributing 28% and gratitude by 75.7%. The remaining 46.3% is influenced by other variables outside this study. This means that every 1% increase in self-esteem will increase optimism by 28%, as well as with the thanksgiving, every 1% increase in gratitude will increase optimism by 75.7%. The results of the F test (42.289) > F table (3.12) and a significance value of 0.000 <0.05, the analysis shows that self-esteem and gratitude together influence optimism so that the Ha3 hypothesis is accepted, which means that self-esteem and gratitude together influence optimism. Based on these findings, BK teachers need to develop programs to improve students' self-esteem and gratitude to increase their optimism, so that students can be more confident and positive in facing challenges.